Luminescent properties of Eu³⁺ doped layered perovskite-like polycrystalline powders of the BaLa₂₋ₓEuₓTi₃O₁₀ (x = 0-2) titanate compounds - Nedilko, S.; Nedielko, I.; Scherbatskii, V.; Titov, Yu.; Virko, S.; Boyko, V.; Sheludko, V. (Functional Materials, 2012)
The photoluminescent properties of concentration set of barium and lanthanum titanium compounds doped with europium ions, BaLa₂₋ₓEuₓTi₃O₁₀, where x = 0-2, were investigated. It was found that the luminescence of mentioned materials is caused by ⁵D₀ —> ⁷Fj (J = 0, 1, 2, 3 and 4) radiation transitions in luminescence centers formed by Eu³⁺ ions. Two types of luminescence centers which differ by symmetry of neighborhood of Eu³⁺ ions were found in luminescent emission. It was shown that luminescent characteristics of Eu³⁺ ions are in close relation with their content in BaLa₂₋ₓEuₓTi₃O₁₀ compounds that can be caused by both changing their crystal structure and phase composition when the ratio of La³⁺ and Eu³⁺ ions is changed.